An unusual cause of recurrent chest pain in an adult woman: a case of recurrent stress-induced (Takotsubo) cardiomyopathy - Mainali, Naba Raj (BMJ Publishing Group, 2013)
Recurrent Takotsubo cardiomyopathy is a relatively uncommon condition seen in patients with severe physical or emotional stress. We report a case of a 51-year-old woman who had recurrent Takotsubo cardiomyopathy with involvement of apical left ventricular (LV) segments, induced by intense emotional stress. On two occasions she presented with symptoms of acute coronary syndrome accompanied by LV regional wall motion abnormalities without a culprit coronary stenosis, and exhibited complete resolution of symptoms and restoration of normal LV wall motion.